An intersectional approach to media coverage of politics in New Zealand: The case of Metiria Turei and Paula Bennett. Issue 1 (May 2023) - Galy-Badenas, Flora; Gray, F Elizabeth; Cassidy, Fiona
This study analyses media coverage of two Māori women politicians in Aotearoa New Zealand. This article adopts an intersectional lens to critically examine the discriminatory ideologies at play in mainstream New Zealand media coverage of Metiria Turei and Paula Bennett. The analysis reveals that although the coverage examined in this article presents the Māori heritage of the two women very differently, the coverage pays close attention to both women's gender and bodies while simultaneously diminishing their individuality by folding them into stereotypes. Classification and disempowerment of 'stroppy women'/'stirrer Māori' are enabled by the intersection of racist, sexist and classist discourses.